Efeito das condições de preparação da [CTA+]-SiMCM-41 na atividade da transesterificação - Cruz, Fernanda Tátia (2010)
The hybrid [CTA+]-SiMCM-41 mesoporous material (where CTA+ is the cetyltrimethylammonium cation) was employed as synthesized in the transesterification reaction between ethyl acetate and methanol. This is a model reaction to test catalysts for the production of biodiesel from vegetable oils and fats. The basic sites of this catalyst were identified as the siloxy anions, generated by the presence of CTA+ cations (≡SiO-CTA+). As the MCM-41 pores are obstructed by these cations the catalytic reaction occurs probably at the pore mouth. The aim of this work was to evaluate different methods of synthesis, studying the effect of thermal parameters treatment (time and temperature) in the activity of as synthesized catalysts. It was observed that the catalytic activity performance is directly related with a better hexagonal structure organization of the samples, then the most organized mesoporous phase presents a larger amount of organized pores. Therefore, the catalytic sites (anions ≡SiO -) are more accessible to catalyze the reaction.